Mubarak criminal liability: is it a fair trial after the revolution or a drama series? - Arafa, Mohamed (Revista Contraponto, 2014)
Divided in four parts, this article will describe a succinct background of former President Mubarak in history, military, and politics and why the Egyptian Revolution had been broken against him and his regime as well. Then will provide the main rules and principles of the leadership’s liability through comparing this concept under Islamic law and the domestic law (Egyptian Penal Code) and how to apply those legal principles to the recent case of Mubarak’s trial which known by the Media as a “Trial of the Century.” At the end of the article looks to the future of this responsibility in light of recent developments throughout the whole Middle East.